Retorika dakwah KH Syukron Djazilan pada pengajian rutin masjid Rahmat Kembang Kuning Surabaya - Ach Tofan Alvino (Faculty of Dakwah and Communication, Walisongo State Islamic University, 2021)
This paper describes the da'wah rhetoric delivered by KH Syukron Djazilan through regular recitations. By knowing the preaching rhetoric of KH Syukron Djazilan as a topic of discussion, an overview of his preaching rhetoric application is expected to got, especially in routine recitations. In addition, the da'wah rhetoric presented by KH Syukron Djazilan can be used as a comparison material to the da'wah development for novice preachers. The method used in this study is a qualitative method with descriptive analysis based on the canon of rhetoric theory. The data collection techniques are conducted by observation and documentation through interviews. Observation by observing the preaching rhetoric of KH Syukron Djazilan in one of the themes presented in routine recitations at the Rahmat Kembang Kuning Mosque in Surabaya. The results of this research show that KH Syukron Djazilan has applied the canons of rhetoric in preaching (discovery, arrangement, style, delivery, and memory). However, KH Syukron Djazilan has prepared everything. He is also fluent in speaking and used it frequently, sometimes repeating his words when giving a religious lecture and it is fair-minded. This research have implicaiton that rhetoric in preaching is a must. It will be better includes unique public speaking skill (humorous) to gain the attention.***Tulisan ini menjelaskan retorika dakwah yang disampaikan oleh KH Syukron Djazilan melalui pengajian rutinan. Dengan mengetahui retorika dakwah KH Syukron Djazilan pada salah satu topik pembahasan, diharapkan akan memperoleh gambaran tentang penerapan retorika dakwah beliau khususnya pada pengajian rutinan. Di samping itu, retorika dakwah yang disajikan oleh KH Syukron Djazilan dapat dijadikan sebagai bahan perbandingan bagi pengembangan dakwah untuk para pendakwah pemula. Metode yang digunakan dalam penelitian ini adalah metode kualitatif dengan analisis deskriptif berdasarkan teori kanon retorika. Adapun teknik pengumpulan datanya melalui observasi dan dokumentasi serta wawancara. Observasi dengan cara mengamati retorika dakwah KH Syukron Djazilan dalam salah satu tema yang disampaikan dalam pengajian rutin di Masjid Rahmat Kembang Kuning Surabaya. Hasil riset ini menunjukkan bahwa KH Syukron Djazilan telah menerapkan kanon retorika dalam berdakwah yaitu (penemuan, pengaturan, gaya, penyampaian, dan ingatan). Namun demikian, KH Syukron Djazilan sudah menyiapkan segala sesuatunya, dan juga sudah lancar berbicara dan terbiasa, ada kalanya mengulangi ucapan ketika berceramah, dan hal tersebut merupakan yang wajar saja. Penelitian ini memiliki implikasi bahwa retorika dakwah itu perlu, akan lebih baik ketika disertai keahlian berbicara di depan umum yang unik (humoris) untuk menarik perhatian.